2005
DOI: 10.1302/0301-620x.87b6.15920
|View full text |Cite
|
Sign up to set email alerts
|

One-stage exchange shoulder arthroplasty for peri-prosthetic infection

Abstract: There are few reports in the literature of the diagnosis and treatment of the infected shoulder arthroplasty. Most deal with resection arthroplasty and two-stage exchange surgery. We present our results of one-stage exchange operation as treatment for the infected shoulder arthroplasty. Our group comprised 16 patients (ten men, six women) with 16 infected arthroplasties. By the time of follow-up, two patients had died (mean 5.8 years), two could not be located and three had already undergone revision surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
83
1
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(98 citation statements)
references
References 10 publications
6
83
1
8
Order By: Relevance
“…Control of infection continues to be the primary goal, and various treatment options have been reported in the literature, including long-term antibiotics, débridement with retention of prosthesis, resection arthroplasty, singlestage exchange, and delayed reimplantation [1,3,7,11,13,14]. The high rates of recurrent infection with IV antibiotics alone or débridement with retention of components (up to 65% [1,10]) have led surgeons to explore alternative treatment options, such as resection arthroplasty, which however is associated with substantial functional limitations [1,4,10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Control of infection continues to be the primary goal, and various treatment options have been reported in the literature, including long-term antibiotics, débridement with retention of prosthesis, resection arthroplasty, singlestage exchange, and delayed reimplantation [1,3,7,11,13,14]. The high rates of recurrent infection with IV antibiotics alone or débridement with retention of components (up to 65% [1,10]) have led surgeons to explore alternative treatment options, such as resection arthroplasty, which however is associated with substantial functional limitations [1,4,10].…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports [3,4,7,14], expectation for postoperative function after periprosthetic shoulder joint infection always focused on quality of the rotator cuff tissues. Clearly a reverse shoulder arthroplasty provides a possible solution in this clinical setting as it relies primarily on deltoid muscle function to determine function [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A retrospective, multicenter study found that infection was eradicated in 82 % of patients using the PROSTALAC implant, while 57 % underwent successful two-stage reimplantation [79]. Ince et al managed 16 patients with infected shoulder arthroplasties with a single-stage method and found no recurrence of infection [80]. Sperling et al treated three patients with prosthetic infection using a twostage method and found no recurrence of infection.…”
Section: Infectionmentioning
confidence: 99%